PENGARUH PEMBELAJARAN KEWIRAUSAHAAN DAN PRAKTIK KERJA LAPANGAN (PKL) TERHADAP MINAT SISWA UNTUK BERWIRAUSAHA DI SMK NEGERI 4 PANDEGLANG - Kurnia, Entin; Sonjaya, Trisna (NIAGARA Scientific Journal, 2024)
Education at the Vocational High School (SMK) level is indeed made and designed by the Government, in this case the Ministry of Education of the Republic of Indonesia is made different from Senior High School (SMA). At the vocational level, students are equipped with Field Work Practice (PKL) programs with the aim that students are able to compete in the industrial or business world. In addition, SMK also teaches Entrepreneurship material which aims to make students have an interest in entrepreneurship in the future. This study aims to determine how influential entrepreneurship learning materials and fieldwork practice activities (PKL) are on the interest in entrepreneurship in students within SMK Negeri 4 Pandeglang, especially in students of Office Management & Business Services / MPLB class XI and XII expertise programs totaling 135 people. By using descriptive research methods with a quantitative approach, the following research results were obtained: 1). Entrepreneurial learning with an entrepreneurial interest of 0.692 shows a strong relationship between the two variables. Meanwhile, based on KD scores, entrepreneurship learning (X1) affects entrepreneurial interest (Y) by 47.88%. While the remaining 52.11% was influenced by other factors; 2). Field Work Practice (PKL) on entrepreneurial interest in obtaining a correlation value of 0.577, which shows that there is a relationship between fieldwork practice and entrepreneurial interest, with the relationship that occurs is strong and positive. Meanwhile, based on the KD value, fieldwork practices (X2) affect entrepreneurial interest (Y) by 33.29%. While the remaining 66.71% was influenced by other factors; 3). Based on the calculation results of the SPSS program version 27.0.1, an R2 value of 0.541 was obtained with a Fcalculate value of 77,734 while Ftable with a significance level of 5% obtained the numerator degree k = 2 and df = n-k-1 = 135-2-1 = 132, then the Ftable value was obtained at 0.32629. The result of Fcalculate (77.734) > Ftabel (3.06), thus Ha is accepted and Ho is rejected. Apart from the table above, it can be seen that the probability value of 0.000 means that this number is smaller than the significance level (0.000 < 0.05). Thus, entrepreneurship learning and fieldwork practices together are significant to the interest in entrepreneurship at SMK Negeri 4 Pandeglang.